ANALYSIS OF THE COLLATERAL AUCTION SYSTEM AT BANK ACEH SYARIAH IN THE PERSPECTIVE OF FIQH MUAMALAH - Zein, Indah Sari (JURISTA: Jurnal Hukum dan Keadilan, 2017)
PT Bank Aceh Syariah must be accommodating or able to act as a mediator and be able to collaborate with various companies related to the community's economy. One of the new business fields offered by PT. Bank Aceh Syariah and which is quite popular with the public is Arrum BPKB, namely loans (credit) for a certain period of time using a fiduciary credit guarantee structure. PT. Bank Aceh Syariah as a distributor of credit funds to the community does not always run well, there are times when debtors do not fulfill their obligations according to the agreed time (default). First, what is the collateral customer system at Bank Aceh Syariah? secondly, how is the price mechanism determined for collateral customers at Bank Aceh Syariah Banda Aceh? Third, what is the validity of providing customers with collateral at Bank Aceh Syariah from the perspective of muamalah fiqh? The research method uses descriptive analysis using primary data in the form of direct interviews at the relevant agencies (field research) using interview and observation techniques as well as library research (library research). The research results show that auctions at Bank Aceh Syariah are carried out formally, namely at the auction hall or the State Property and Auction Service Office (KPKNL). The bank will auction off the collateral as much as the collateral that the bad customer can no longer afford. Auctions in muamalah fiqh are also called muzayadah and their implementation is almost the same as auctions held at KPKNL. Auctions are a form of buying and selling, but there are general differences. Buying and selling has the right to choose, while auctions do not have the right to choose, and the implementation is carried out specifically in public. Buying and selling using the auction model (muzayadah) in Islamic law is permissible.